A influência das heurísticas nas decisões projetuais de designers em formação - Fontanella, Luiza Leal (Universidade do Vale do Rio dos Sinos, 2017)
Heuristics are general rules of influence that act on people's decisions. Recent studies show that they interfere in designers' project decisions, either through the use of memory or imagination (heuristics of availability), or through judgments by similarity (heuristics of representativeness). Because designers deal with uncertain problems, its possible to realize the importance of these professionals being aware of the process involving such intuitive judgments. It is believed that the teaching of intuitive self-knowledge during the formative years of designers has the potential to prepare them to project with greater awareness of the cognitive processes involved in their practices. In this sense, the present study proposed, as a general objective, to understand the operation of heuristics in design students in design decisions during their first and last year of formation. For that, an exploratory research with in-depth interviews was developed, trying to understand the problem through the perceptions of the students of design itself. As main results, it was noticed that heuristics act in the designers in formation, throughout the entire design process. In addition, they proved to be more present than reasoning in making project decisions. As for the difference about the influence of the heuristics between the students at the beginning and end of the course, it was observed that the last year students of had perceptions about some heuristic influences. But, because they had no knowledge of the intuitive process, or of the heuristics, they did not know how to manage such influences. Thus, it was understood the importance of design education institutions to encourage the development of intuition, seeking to integrate it to the skills worked in their education programs.
Keywords: Intuição; Processos cognitivos; Educação em design; Design intuition; Intuition; Cognitive processes; Design education; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial